Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1086/378688
|View full text |Cite
|
Sign up to set email alerts
|

The Mass, Baryonic Fraction, and X‐Ray Temperature of the Luminous, High‐Redshift Cluster of Galaxies MS 0451.6−0305

Abstract: We present new Chandra X-ray observations of the luminous and cosmologicallysignificant X-ray cluster of galaxies, MS0451.6-0305, at z = 0.5386. Spectral imaging data for the cluster are consistent with an isothermal cluster of (10.0 − 10.6) ± 1.6 keV, with an intracluster Fe abundance of (0.32−0.40)±0.13 solar. The systematic uncertainties, arising from calibration and model uncertainties, of the temperature determination are nearly the same size as the statistical uncertainties, since the time-dependent corr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
47
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 76 publications
9
47
0
Order By: Relevance
“…if we only consider systems exactly like we found, then the probability would be arbitrarily small), we can carry out a crude estimate as follows. The MS0451 cluster has a mass of around 10 15 M (Donahue et al 2003) and an Einstein radius of around 30 arcsec. Conservatively taking 3 × 10 14 M as the limit for rich clusters, surveys (like the Planck catalogue of Sunyaev-Zeldovich sources; Planck Collaboration XXIX 2013) suggest that there are around 2000 such clusters on the sky, and hence the sum of the areas covered by their Einstein radii (where strong lensing is possible) is about 10 −5 of the sky.…”
Section: R E S U Lt S a N D Discussionmentioning
confidence: 99%
“…if we only consider systems exactly like we found, then the probability would be arbitrarily small), we can carry out a crude estimate as follows. The MS0451 cluster has a mass of around 10 15 M (Donahue et al 2003) and an Einstein radius of around 30 arcsec. Conservatively taking 3 × 10 14 M as the limit for rich clusters, surveys (like the Planck catalogue of Sunyaev-Zeldovich sources; Planck Collaboration XXIX 2013) suggest that there are around 2000 such clusters on the sky, and hence the sum of the areas covered by their Einstein radii (where strong lensing is possible) is about 10 −5 of the sky.…”
Section: R E S U Lt S a N D Discussionmentioning
confidence: 99%
“…This reduces the scatter in mid-IR color due to star formation for members. X-ray data have shown that the distribution of the cluster ICM is predominantly elliptical (Donahue et al 2003) and the redshift distribution of cluster galaxies is broadly Gaussian (Moran et al 2007a). This indicates that MS 0451 is predominantly virialized with no substantial infalling galaxies.…”
Section: Ms 0451-03mentioning
confidence: 99%
“…However, the low X-ray fluxes of typical high-redshift clusters make the observing time needed to meet these requirements prohibitive. Sufficiently deep observations for clusters at z > 0:5 are very rare (e.g., Jeltema et al 2001;Arnaud et al 2002;Donahue et al 2003;Maughan et al 2004b); for most clusters at high redshifts, masses must be estimated from observed global properties such as X-ray luminosity and temperature. The scaling relations between cluster properties at high redshifts are then of key importance, and their uncertainty is a dominant contributor to the error budget of derived cosmological parameters (Henry 2004).…”
Section: Introductionmentioning
confidence: 99%